CHEMICAL CHARACTERISTICS OF SORGUM (Sorgum bicolor) TEMPEH WITH SUBSTITUTION OF GUDE BEAN (Cajanus cajan) - Dewi, Mira Kurniawati; Handayani, Anna Mardiana (Universitas Negeri Gorontalo, 2025)
Tempeh is a traditional food processed using a fermentation method to produce a distinctive flavor. Tempeh is made with soybeans as the main ingredient. Currently, it is often made by mixing legumes such as cowpeas, red beans, mung beans, and sorghum. Sorghum tempeh can be made using pigeon peas, but no research has ever been conducted on the chemical characteristics of sorghum tempeh with pigeon pea substitution. The purpose of this study was to chemically characterize sorghum tempeh with pigeon pea substitution and fermentation times of 48 and 72 hours. The study used a completely randomized design with two factors: variations in the level of pigeon pea substitution and fermentation time, resulting in eight treatments. The research parameters observed were water, ash, protein, fat, and carbohydrate content. The results showed that pigeon pea substitution and fermentation affected protein content, but did not affect water, ash, fat, or carbohydrate content. Fermentation time can increase water, protein, and carbohydrate content.